Visual Studies and an analysis proposal for the (tele)visualities - Rocha, Simone Maria (2016)
This paper presents a proposal of an analysis of televisual products that works in non-dissociation of this medium’s formal and cultural dimensions. Such effort implies taking into account the complexity of television, its recognized cultural value and specificity of its products. Therefore, we adopt the theoretical and methodological central notion of visuality such as presented by the visual studies perspective.